2021
DOI: 10.21203/rs.3.rs-757455/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity and efficacy of heterologous ChadOx1/BNT162b2 vaccination

Abstract: Following severe adverse reactions in patients vaccinated with the AstraZeneca ChadOx1 (Chad) vaccine, European health authorities have recommended that patients under the age of 55 who received one dose of Chad vaccine receive a second dose of Pfizer BNT162b2 (BNT) vaccine as a booster. However, the effectiveness and the immunogenicity of this vaccination regimen have not been formally tested. Here, we show that the heterologous Chad/BNT combination confers better protection against SARS-CoV-2 infection than … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 16 publications
(20 reference statements)
7
45
0
Order By: Relevance
“…Our findings on heterologous schedules involving ChAdOx1 and BNT162b2 supports earlier findings from studies predominately from Europe where priming of ChAdOx1 and boosting with BNT162b2 as the second dose induced higher humoral and cell-mediated immune responses than homologous ChAdOx1 primary series 11,12,[15][16][17] , and to some extent higher cell-mediated immune responses than homologous BNT162b2 primary series. Some studies have found better neutralising capacity against the SARS-CoV-2 variants and immune memory responses following heterologous ChAdOx1-BNT162b2 schedule compared to homologous ChAdOx1 or BNT162b2 18 . Whether other combinations of heterologous COVID-19 vaccination, including longer intervals between different vaccines can improve protection against SARS-CoV-2 variants is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings on heterologous schedules involving ChAdOx1 and BNT162b2 supports earlier findings from studies predominately from Europe where priming of ChAdOx1 and boosting with BNT162b2 as the second dose induced higher humoral and cell-mediated immune responses than homologous ChAdOx1 primary series 11,12,[15][16][17] , and to some extent higher cell-mediated immune responses than homologous BNT162b2 primary series. Some studies have found better neutralising capacity against the SARS-CoV-2 variants and immune memory responses following heterologous ChAdOx1-BNT162b2 schedule compared to homologous ChAdOx1 or BNT162b2 18 . Whether other combinations of heterologous COVID-19 vaccination, including longer intervals between different vaccines can improve protection against SARS-CoV-2 variants is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of heterologous schedules in this study is unknown, however protection is likely to be similar or greater than homologous schedules given the association between humoral responses and vaccine efficacy 9,22 . Indeed, a recent observational study on the immunogenicity and efficacy of ChAdOx1-BNT162b2 vaccination found that this schedule provided better protection against SARS-COV-2 infection, including the variants (Omicron not tested) than the homologous BNT162b2 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study adds to a molecular understanding of findings that a heterologous ChAdOx1-BNT162b2 vaccination schedule promotes a more robust immune response than two doses of either BNT162b or ChAdOx1 2-4 . While several ChAd-ChAd heterologous vaccination studies 5,6 , including from South Korea 11,31 , have been published, this is the first report investigating the molecular immune response using bulk and single cell RNA-seq as well as the antibody response to different variants, including the fast-spreading Omicron.…”
Section: Discussionmentioning
confidence: 69%
“…This promoted partially vaccinated people to complete their vaccination with an mRNA vaccine, Pfizer/BioNTech (BNT) or Moderna. The ChAd-BNT heterologous vaccination strategy resulted in significantly greater immunoglobulin G (IgG) immune responses aimed against the SARS-CoV-2 spike protein compared to the ChAd-ChAd strategy [2][3][4][5][6][7] . While the immune response to different vaccine regimen has been investigated, there is limited knowledge about the molecular transcriptome responses, elicited by heterologous vaccinations.…”
Section: Introductionmentioning
confidence: 99%